Effect of Customer Experience and Customer Value Towards Customer Loyalty and Satisfaction on B2B Food and Beverage Sector - Kristianus Ade Sudiyono; Prio Utomo; Claudia Severesia (Journal of Business and Management Review, 2022)
This study aims to study the effect of customer experience and value on customer loyalty and satisfaction in B2B industry which researchers limitedly discussed. The organization needs to implement customer experience management to create value for customers' purchase intention and win the market competition. One essential key to maintaining customer loyalty is good customer experience management. The elements of customer experience management consist of customer experience, customer value, and purchase intention. The research is cross-sectional quantitative research. An online survey using Google Form was carried out using the purposive sampling technique in 2021 and obtained 85 valid respondents who are corporate customers of a food and beverage manufacturing company located in Tangerang. Respondents were asked 23 closed ended on five scales Likert: strongly disagree to strongly agree. Data were analyzed using PLS-SEM (Partial Least Square – Structural Equation Model. The result shows that customer experience significantly affects customer value, loyalty, and satisfaction. Customer value significantly affects customer loyalty but is not significant to customer satisfaction. Customer experience involves the customer's response to the customer's journey. However, the nature of customer experience is quite complicated; therefore, measurement of customer satisfaction and customer loyalty is used more often. Customer value is related to the company’s product excellence, which has a long-term effect resulting in customer loyalty. Therefore, organizations need to focus on building customer experience management and long-term customer value.